« Coast, to coast… to coast ». Le rôle des francophonies boréales dans l’accueil, l’installation et la rétention des migrants francophones au Yukon, aux Territoires du Nord-Ouest et au Nunavut - Traisnel, Christophe (Études canadiennes / Canadian Studies, 2015)
This article presents one of the main results of a research conducted on francophone communities in Nunavut, Yukon and the Northwest Territories, namely the essentially migratory character of these communities and the impact of this dimension on the vitality of “francophonies boréales”. The situation of these linguistic minorities is very particular: in constant contact with indigenous communities, these francophonies have developed a dynamic associative life in a context marked not by an official bilingualism (as elsewhere in Canada), but by territorial multilingualism, French enjoying, like English and the other indigenous languages present, official recognition in the territories. This paper shows that if these francophones “coming from elsewhere” and even different “elsewheres” (i.e. Europe, Africa .), most of them also plan to go back one day. We report on the dynamics in regards to the welcoming of francophone migrants, as well as the impact of this aspect of migration on the lives of Francophone communities, but also the very particular context of the Canadian “boréales societies”. Cet article présente l’un des principaux résultats d’une recherche effectuée sur les communautés francophones situées au Nunavut, au Yukon et dans les Territoires du Nord-Ouest, à savoir le caractère essentiellement migratoire de ces communautés et l’impact de cette dimension sur la vitalité des francophonies boréales. La situation de ces minorités linguistiques est très particulière : en contact constant avec les communautés autochtones, ces francophonies ont développé une vie associative dynamique dans un contexte marqué non par un bilinguisme officiel (comme ailleurs au Canada), mais par un plurilinguisme territorial, le français jouissant dans les territoires d’une reconnaissance officielle, à l’instar de l’anglais, mais également des autres langues autochtones présentes. Cet article montre que si ces francophones « viennent d’ailleurs » et même de divers ailleurs (Europe, Afrique…), la plupart d’entre eux envisagent ...